2020
DOI: 10.1519/jsc.0000000000002628
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Self-Myofascial Release vs. Instrument-Assisted Soft-Tissue Mobilization Techniques on Vertical and Horizontal Power in Recreational Athletes

Abstract: Stroiney, DA, Mokris, RL, Hanna, GR, and Ranney, JD. Examination of self-myofascial release vs. instrument-assisted soft-tissue mobilization techniques on vertical and horizontal power in recreational athletes. J Strength Cond Res XX(X): 000-000, 2018-This study examined whether pre-exercise self-myofascial release (SMR) and instrument-assisted soft-tissue mobilization (IASTM) would improve performance on measures of vertical jump height and 40-yd sprint time. Differences in perceived pain levels were also exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…However, unlike ROM, performance results obtained were not always clearly established (Burk et al, 2019;Hughes and Ramer, 2019;Skinner et al, 2020). Some studies recorded improvements in muscle power, strength or agility, after a single session of FR (D'Andrea, 2016;Sagiroglu, 2017;Stroiney et al, 2020). Other came to different conclusions.…”
Section: Short-term Effectsmentioning
confidence: 98%
“…However, unlike ROM, performance results obtained were not always clearly established (Burk et al, 2019;Hughes and Ramer, 2019;Skinner et al, 2020). Some studies recorded improvements in muscle power, strength or agility, after a single session of FR (D'Andrea, 2016;Sagiroglu, 2017;Stroiney et al, 2020). Other came to different conclusions.…”
Section: Short-term Effectsmentioning
confidence: 98%
“…Furthermore, two studies analysed the changes in a vertical jump test (sergeant jump) after the inclusion of myofascial release. Stroiney et al [ 68 ] found significant differences in a group of 49 athletes in a vertical jump test after the application of a myofascial self-release programme (+2.54 ± 3.2 cm, p = 0.04), reflecting a greater increase than a group performing an instrument-assisted soft-tissue mobilisation protocol, though those did not reach significant differences. On the other hand, Peacock et al [ 78 ] found significant differences in a sample of 11 NCAA tournament athletes (Division I and Division II) from different disciplines ( p = 0.012), finding no differences in the group that performed mobility work without the inclusion of an FR.…”
Section: Resultsmentioning
confidence: 99%
“…In this systematic review, 25 studies in total were identified [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ], examining the use of different SMR techniques before and after exercise and also as a recovery method. Each study applied different exercise protocols, using various treatments, application times, and measures and assessing different results, which made the selection of results a challenge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations